China's monetary policy and the loan market: How strong is the credit channel in China? - Max Breitenlechner; Riikka Nuutilainen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
We study the credit channel of Chinese monetary policy in a structural vector autoregressive framework. Using combinations of zero and sign restrictions, we identify monetary policy shocks linked to supply and demand responses in the loan market. Our results show that policy shocks coinciding with loan supply effects account for roughly 10 percent of output dynamics after two years, while loan demand effects represent up to 7 percent of output dynamics depending on the policy measure. The credit channel thus constitutes an important and economically relevant transmission channel for monetary policy in China. Monetary policy in China also accounts for a relatively high share of business cycle dynamics.
URN:NBN:fi:bof-201908121387
Keywords: C32; E44; E52; 330; China; Monetary Policy; Transmission Effects; Structural Vector Autoregression; Zero and Sign Restrictions